Effective periods and seismic performance of steel moment resisting frames designed for risk categories I and IV according to IBC2009. (5th December 2014) - Jeong, Seong‐Hoon; Kwon, Oh‐Sung; Lee, Kwang‐Ho
Summary In current seismic design, structures that are essential for post‐disaster recovery, and hazardous facilities are classified as risk category IV and are designed with higher importance factors and stringent drift limits. These structures are expected to perform better in an earthquake event because a larger base shear and more stringent drift limit are used. Although this provision has been in the seismic design code over the last three decades, few studies have investigated the performance of essential structures. The aim of this study is to quantify the impact of higher importance factors and stringent drift limits on the seismic performance of steel moment resisting frames. A total of 16 steel structures are designed for Los Angeles and Seattle. Different risk categories are used for the design. The effects of the risk categories on the structural periods, and thus on the seismic force demand, are investigated. A suite of inelastic time history analyses are carried out to understand the probability of exceeding a specified limit state when the structures are subjected to different levels of earthquake events. The results show that the periods of the structures in risk category IV decrease by a factor of 0.5 to 0.8, and the strengths increase by a factor of 1.5 to 3.2. Seismic fragility analysis shows that the structures in risk category IV generally satisfy the probabilistic performance objectives. Copyright © 2014 John Wiley & Sons, Ltd.